PM10 prediction for brake wear of passenger car during different test driving cycles. (October 2022) - Liu, Ye; Chen, Haibo; Yin, Chuhan; Federici, Matteo; Perricone, Guido; Li, Ying; Margaritis, Dimitris; Shen, Yang; Guo, Junhua; Wei, Tangjian
Abstract: PM10 emissions generated from the brake wear of passenger car per braking event during three test driving cycles (WLTP, LACT, and WLTP-Brake) were studied using a finite element analysis (FEA) approach in combination with the relationship among the mass emitted rate of airborne particles versus local contact pressure and sliding speed. In addition, PM10 emissions were measured per braking event during the WLTP-Brake cycle on a brake dynamometer using an electrical low-pressure impactor (ELPI+) to validate the proposed FEA approach. The simulated and experimental results for WLTP-Brake illustrated that the proposed simulation approach has the potential to predict PM10 from brake wear per braking event, with an R 2 value of 0.93. The FEA results of three test driving cycles showed that there was a gradient rise in pad wear on both sides from the inner to outer radii. The simulated PM10 emission factors during the WLTP, LACT, and WLTP-Brake were 7.9 mg km −1 veh −1, 9.8 mg km −1 veh −1, and 6.4 mg km −1 veh −1, respectively. Among three test driving cycles, the ratio of PM10 to total brake wear mass per braking event was the largest for the LACT, followed by WLTP and WLTP-Brake. From a practical application perspective, reducing the frequency of high-speed braking may be an effective way to decrease the generation of PM10 emissions. Graphical abstract: Image 1 Highlights: Brake wear PM10 emissions under three test driving cycles were studies using FEA. PM10 emissions were measured on a brake dynamometer to validate FEA approach. PM10 EFs under the WLTP, LACT, WLTP-Brake were 7.9, 9.8, and 6.4 mg km −1 veh −1 . PM10 EFs showed a greater fraction of total mass EFs in LACT than other two cycles.